Robot-Assisted versus Conventional Total and Unicompartmental Knee Arthroplasty: A Meta-analysis of Radiological and Functional Outcomes - Chin, Brian Zhaojie; Tan, Sharon Si Heng; Chua, Kasia Chen Xi; Budiono, Gideon Richard; Syn, Nicholas Li-Xun; O'Neill, Gavin Kane (The Journal of Knee Surgery, 2020)
The study aims to provide an up-to-date systematic review and meta-analysis comparing radiological and functional outcomes of total knee arthroplasty (TKA) and unicompartmental knee arthroplasty (UKA) using either robotic assistance or conventional methods from the latest assemblage of evidence. This study was conducted according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and MOOSE (Meta-analysis of Observational Studies in Epidemiology) guidelines. All studies in PubMed, EMBASE, Medline, and Cochrane that reported radiological and functional outcomes after TKA or UKA with either robotic or conventional methods were included in the review. Selected endpoints for random effects, pairwise meta-analysis included operative details, radiological outcomes (mechanical axis, component angle deviation, and outliers), and functional outcomes (American Knee Society Score, Knee Society Function Score, revision and complication rate, range of motion (ROM), Hospital for Special Surgery score, and Western Ontario and McMaster Universities Osteoarthritis Index). A total of 23 studies comprising 2,765 knees were included from the initial search. Robot-assisted TKA and UKA were associated with significantly better component angle alignment accuracy (low-to-high quality evidence) at the cost of significantly greater operation time. Robot-assisted UKA was found to have significantly better short-term functional outcomes compared with conventional UKA (moderate-to-high quality evidence). Robot-assisted TKA, however, did not exhibit significantly better short- and midterm subjective knee outcome scores compared with its conventional counterpart (high-quality evidence). Robot-assisted TKA and UKA were associated with nonstatistically significant improved ROM and lesser rates of revision. Robot-assisted total and unicompartmental knee arthroplasty leads to better radiological outcomes, with no significant differences in mid- and long-term functional outcomes compared with conventional methods for the former. Larger prospective studies with mid- and long-term outcomes are required to further substantiate findings from the present study.
Keywords: robot-assisted; conventional; total knee arthroplasty; unicompartmental knee arthroplasty; functional outcomes; radiological outcomes